IMPROVEMENT OF ESTABLISHING METHOD IN NORMAL AND DWARF VARIETIES OF ELEPHANTGRASS FORAGE FIELD - mukhtar muhammad (Universitas Negeri Gorontalo, 2014)
Improvement of Establishing Method in Normal and Dwarf Varieties of Elephantgrass Forage Field. For determining the establishment method by transplanting nodal positions of tiller bud were compared in a normal (cv. Wruk wona) and two dwarf varieties (dwarf-early type, DE and dwarf-late type, DL) of Elephantgrasses. The position of tiller bud measured was odd number from 1 to 19 in Wr and DL by dividing into two nodes, and every number from 1 to 10 in DE by dividing into a single node because of a limited number of tiller buds per tiller. The order of internode dry matter weight (DMW) was larger in dwarf DE followed by normal Wr and dwarf DL. Percentage seedling emergency (PSE) was larger in dwarf varieties than normal Wr. Regrown tiller number (RTN) was larger in dwarf varieties than normal Wr, however, the position of that node number to that RTN was negatively relationship (P